PENGARUH TEKNOLOGI INFORMASI, KOMPETENSI DAN PROFESIONALISME TERHADAP KINERJA PEGAWAI INSPEKTORAT KABUPATEN BARRU - Musfira Musfira; Muhammad Idris; Hery Sugeng Waluyo (Nobel Management Review, 2020)
This study aims to: analyze Information Technology, Competence and Professionalism partially influence the performance of Employees in the Barru District Employment Work and to analyze Information Technology, Competence and Professionalism simultaneously influence the performance of Employees at the Barru District Inspectorate. The sample of this study was using a saturated sample in which samples were taken from all populations, namely the entire 34 civil servants Barru District Inspectorate. The results of this study indicate that partially the work culture has a significant effect on the analyze Information Technology with a t count of 2.172 with sig.0.038, has a Competence significant effect on the obtained t count of 4.019 with sig.0.000, has a Professionalism significant effect on the performance of Employee obtained t count for 2.363 with sig.0,025. While simultaneously can analyze Information Technology, Competence and Professionalism affect the employee performance of 54.1% (adjusted r square = 0.541). The partial correlation of analyze Information Technology by 0.278, the partial correlation of Competence by 0.512 and the partial correlation of Professionalism by 0.296, which means job satisfaction has a greater influence on employee performance of the Barru District Inspectorate